Comparação de técnicas de controle de velocidade sensorless aplicadas a motores de indução em plataforma DSP - Martins, Orlando Saccol (2006)
This work proposes a comparative performance analysis of control and estimation techniques applied to three-phase induction motors with discrete realization, using a fixed-point digital signal processor based platform. Some modifications in original algorithms are proposed to improve the performance of the techniques in study. Initially, an historical review about the induction motors drives and a bibliographical review of the main speed estimation techniques implemented in DSP were accomplished. Then, different models of the induction machine are obtained using the semi-stationary reference frames. From the machine model, two speed controllers are projected: a classical PI controller, that is widely used in industrial environment and a robust model reference adaptive controller, objecting to compensate disturbances and unmodeled dynamics. After that, two estimation techniques based on 1M model are selected to project high-performance speed sensorless drives and later comparison. One of these schemes is extremely spread in academic and industrial environrnents, it is based on a model reference adaptive system (MRAS) and the other one is projected from a modified recursive least squares (MRLS), that is presented as a highperformance altemative solution. In the development of this work are displayed simulation results using the MatlabTM software, real-time simulations in DSP platform, and finally, experimental results. After these results analysis, it is possible to determinate which of these sensorless speed controllers proposed present satisfactory dynamic response for a wide range of speed, including low and null rotations, in situations of load disturbances and parametric variation.